2015
DOI: 10.1155/2015/246792
|View full text |Cite
|
Sign up to set email alerts
|

Late Corrective Arthrodesis in Nonplantigrade Diabetic Charcot Midfoot Disease Is Associated with High Complication and Reoperation Rates

Abstract: Introduction. Charcot arthropathy may lead to a loss of osteoligamentous foot architecture and consequently loss of the plantigrade alignment. In this series of patients a technique of internal corrective arthrodesis with maximum fixation strength was provided in order to lower complication rates. Materials/Methods. 21 feet with severe nonplantigrade diabetic Charcot deformity Eichenholtz stages II/III (Sanders/Frykberg II/III/IV) and reconstructive arthrodesis with medial and additional lateral column support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Patients with CN have a greater risk of infectious and noninfectious complications after surgery (33,34). Although critical limb ischemia might not be present, optimization of perfusion might improve the outcomes of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CN have a greater risk of infectious and noninfectious complications after surgery (33,34). Although critical limb ischemia might not be present, optimization of perfusion might improve the outcomes of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment outcomes and complication rates vary between centres. Late corrective arthrodesis in non‐plantigrade diabetic Charcot foot was associated with high complication and reoperation rates in a series of 19 patients with severe CN . However, we reported recently the outcomes of 20 patients (21 ft) with CN who underwent correction of deformities of the ankle and hindfoot using retrograde intramedullary nail arthrodesis .…”
Section: Managementmentioning
confidence: 99%
“…All patients had active plantar ulceration at the time of operative intervention and 13/15 patients were able to walk with custom-made extra-depth, wide-toed diabetic shoes at the time of final follow-up (average 42 months). 1 In a similar retrospective review of 21 cases of Charcot osteoarthropathy in Germany, Eschler et al 2 reported higher rates of complication following internal fixation: 33% reulceration and 24% amputation at final follow-up (average 4 years). The rates of amputation and reulceration cannot be directly statistically compared those reported by Assal and Eschler given the small sample size of patients in all series.…”
Section: Discussionmentioning
confidence: 98%
“…The rates of amputation and reulceration cannot be directly statistically compared those reported by Assal and Eschler given the small sample size of patients in all series. 1,2 Several authors have published reports of midfoot realignment using external fixators for midfoot osteoarthropathy. 7,12 Pinzur et al 12 report that 24/26 "high-risk" patients in their series are ulcer and infection-free 12 months following multiplanar deformity correction and stabilization in a thin-wire fixator; notably, these patients were also treated with culture-specific parenteral antibiotic therapy when applicable and Achilles lengthening at the time of operative intervention.…”
Section: Discussionmentioning
confidence: 99%